Penerapan Pembelajaran Story telling Berbantu Media Kobe untuk Meningkatkan Minat Baca Siswa V MI Bahrul Ulum Kemlagilor Turi Lamongan - Maharani, Tri Julia; Futaqi, Sauqi (-, 2026)
The reading interest of Indonesians, especially in elementary schools, is currently declining due to the influence of technology and reduced motivation from parents and teachers. This is in line with the ranking results which placed Indonesia in 29th place out of 31 countries studied in Asia. However, reading is important for increasing knowledge, exploring information, and broadening horizons. Therefore, innovative strategies are needed to arouse student interest, such as the application of the story telling method. The objectives of this study are, to determine the application of storytelling learning in SKI lessons in class V MI Bahrul Ulum Kemlagilor Turi Lamongan, and to determine the extent to which the method can increase students’ interest in reading. This research method uses a descriptive qualitative approach. Data collection techniques through observation, interviews, and documentation, involving class V students as research subjects. The data analysis technique used uses the model from Miles, Hubner and Salman which consists of data condensation, data presentation, and drawing conclusions. The story telling learning process includes two stages,namely, the first stage of preparation before storytelling includes selecting a theme and making props, the second stage of storytelling takes place using props with pictures to attract students’ interest in listening to the story. The results obtained in this study indicate that the application of the storytelling method shows an increase in students’ attention, interest in the material, and the desire toread further the stories of Islamic figures conveyed. Thus, storytelling learning is effective in increasing students’ interest in reading, especially in narrative and historical- based SKI lessons.